Transcriptome analysis of wheat spikes in response to Tilletia controversa Kühn which cause wheat dwarf bunt - Zhaoyu Ren (Nature Portfolio, 2020)
Abstract Wheat dwarf bunt is caused by Tilletia controversa Kühn, which is one of the most destructive diseases of wheat worldwide. To explore the interaction of T. controversa and wheat, we analysed the transcriptome profile of spikes of the susceptible wheat cultivar Dongxuan 3, which was subjected to a T. controversa infection and a mock infection. The results obtained from a differential expression analysis of T. controversa-infected plants compared with mock-infected ones showed that 10,867 out of 21,354 genes were upregulated, while 10,487 genes were downregulated, and these genes were enriched in 205 different pathways. Our findings demonstrated that the genes associated with defence against diseases, such as PR-related genes, WRKY transcription factors and mitogen-activated protein kinase genes, were more highly expressed in response to T. controversa infection. Additionally, a number of genes related to physiological attributes were expressed during infection. Three pathways were differentiated based on the characteristics of gene ontology classification. KEGG enrichment analysis showed that twenty genes were expressed differentially during the infection of wheat with T. controversa. Notable changes were observed in the transcriptomes of wheat plants after infection. The results of this study may help to elucidate the mechanism governing the interactions between this pathogen and wheat plants and may facilitate the development of new methods to increase the resistance level of wheat against T. controversa, including the overexpression of defence-related genes.